2020
DOI: 10.1108/jchmsd-08-2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

Applying the MOA (motivation-opportunity-ability) model for the evaluation of residents' participation in built heritage rehabilitation: the case of Constantine

Abstract: PurposeIt has been widely recognised that the participation of residents is a significant issue in contemporary urban heritage conservation. However, studies confirm that the reasons behind residents' engagement are still difficult to assess, particularly in emerging countries. This paper aims to evaluate the factors that incite or prevent residents from participating in built heritage rehabilitation in the old city of Constantine, by applying the motivation-opportunity-ability (MOA) model.Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(85 reference statements)
2
6
0
Order By: Relevance
“…Opportunity is depicted in form of financial resources, cultural exposure, career opportunities, availability of relevant information, and income to enable change in intentions and user behaviour (Ou-Yang et al, 2014). Benedjma and Mahimoud, (2021) in their study reported a strong influence of opportunity on behavioural intentions. On the contrary, Ukenna and Nkamnebe, (2017) findings reported a direct influence of opportunity on user behaviour while Syed Zwick, (2019) findings reported that opportunity mediates the relationship between behavioural intentions and user behaviour.…”
Section: Influence Of Opportunity On Lcis' Ability and Engagement Beh...mentioning
confidence: 80%
See 2 more Smart Citations
“…Opportunity is depicted in form of financial resources, cultural exposure, career opportunities, availability of relevant information, and income to enable change in intentions and user behaviour (Ou-Yang et al, 2014). Benedjma and Mahimoud, (2021) in their study reported a strong influence of opportunity on behavioural intentions. On the contrary, Ukenna and Nkamnebe, (2017) findings reported a direct influence of opportunity on user behaviour while Syed Zwick, (2019) findings reported that opportunity mediates the relationship between behavioural intentions and user behaviour.…”
Section: Influence Of Opportunity On Lcis' Ability and Engagement Beh...mentioning
confidence: 80%
“…Motivation has a direct influence on user behaviour (Syed Zwick, 2019;Bergstrom & Martinez, 2016). Motivation and abilities are the key factors that influence user behaviour (Benedjma & Mahimoud, 2021). Findings of MacInnis, Moorman, and Jaworski, (1991) found that motivation, opportunity, and ability influence user behaviour.…”
Section: Influence Of Motivation On Lcis' Ability and Engagement Beha...mentioning
confidence: 99%
See 1 more Smart Citation
“…In MOA theory, action most likely occurs only if all three components -motivation, opportunity, and ability -are present simultaneously (Rothschild, 1999); these components are prerequisites for participation in activities (Benedjma and Mahimoud, 2020;Jelinek et al, 2006). In tourism activities, tourists' motivation and opportunity are positively related to their participation, but not significantly related to their ability (Leung and Bai, 2013).…”
Section: Moa Theory and Participationmentioning
confidence: 99%
“…Benedjma & Mahimoud, 2020; Boufenara & Belabed-Sahraoui, 2016; Fantazi et al, 2019;Hafiza, 2014;Merouani, 2015;Touam, 2012). Some of this research has focused on the aspect of consultation between stakeholders (Boufenara & Belabed-Sahraoui, 2016) and others were concerned about what factors encourage or prevent people from participating (Benedjma & Mahimoud, 2020). However, the question of the effectiveness of the residents' participation in the process of the operations and its impact on the results has not been addressed, which seems an opportune opening for us to make our contribution.…”
Section: Introductionmentioning
confidence: 99%